Transformasi Pemasaran Digital sebagai Strategi Peningkatan Penjualan Sayuran Organik di Kota Makassar - Rahmah, Nur; Yanto, Subari; Puspitasari, Dewi; Diyahwati, Diyahwati (Indonesian Journal of Social and Educational Studies, 2025)
Abstract. This research aims to analyze the role of digital marketing transformation in improving the sales performance of organic vegetables in Makassar City. The study was motivated by the increasing awareness of healthy food consumption and the rapid advancement of information technology that drives the digitalization of the agricultural sector. The research employed a mixed-method approach, combining quantitative data collection through questionnaires and qualitative analysis through in-depth interviews. A total of 50 organic business actors participated as respondents. Quantitative data were analyzed using simple linear regression to examine the relationship between digital marketing transformation and sales performance, while qualitative data were analyzed thematically to explore supporting and inhibiting factors. The findings indicate that the implementation of digital marketing strategies based on social media and e-commerce increased the average sales volume by 35% within the first three months. Key success factors include content consistency, interactive engagement with consumers, and accessibility of digital transactions. Major challenges were limited digital literacy and high online promotion costs. This study highlights the importance of digital marketing transformation as an effective strategy to expand markets and strengthen the competitiveness of local organic agribusinesses in the digital economy era Keywords: digital marketing, sales, organic vegetables, strategy, transformation